2022
DOI: 10.1186/s43043-022-00107-5
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic differentiation of spermatogonial stem cells on three-dimensional silk nanofiber scaffold

Abstract: Background Nano-fibrous scaffolds provide a three-dimensional matrix that guides sufficient orientation of seeded cells similar to a natural niche. In this research, we designed a silk scaffold to improve the differention of mouse spermatogonial stem cells to spermatogenic cell lines. Spermatogonial stem cells were collected from neonatal mouse (2–6 days) testes (n=60) using a two steps mechanical and enzymatic method. Cells were seeded on a silk scaffold and were cultured in Dulbecco’s modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In recent years, a wide range of synthetic polymers (synthetic carbon [79,80], polycaprolactone [81], poly-L-lactic acid [82,83], polyvinyl alcohol [84], polyamide [85], and glycolic acid [83]) and natural polymers (alginate [86,87], gelatin [88], methyl cellulose [89], collagen [90,91], fibroin [92,93], chitosan [94], Matrigel [95][96][97], and agarose [75,98]) have been used to fabricate scaffolds for the purpose of improving spermatogenesis. Most synthetic scaffolds were found unsuitable for SSC differentiation, whereas natural biomaterials demonstrated superior performance.…”
Section: Ssc Culturementioning
confidence: 99%
“…In recent years, a wide range of synthetic polymers (synthetic carbon [79,80], polycaprolactone [81], poly-L-lactic acid [82,83], polyvinyl alcohol [84], polyamide [85], and glycolic acid [83]) and natural polymers (alginate [86,87], gelatin [88], methyl cellulose [89], collagen [90,91], fibroin [92,93], chitosan [94], Matrigel [95][96][97], and agarose [75,98]) have been used to fabricate scaffolds for the purpose of improving spermatogenesis. Most synthetic scaffolds were found unsuitable for SSC differentiation, whereas natural biomaterials demonstrated superior performance.…”
Section: Ssc Culturementioning
confidence: 99%
“…Number of spermatogonial stem-like cell colonies was significantly higher than control group after transplantation into the seminiferous tubules of busulfan-treated adult mice. Narimanpouret al [ 153 ] Mouse testicular cells Silk scaffold 1 week Expression of VASA, DAZL, and Piwil2 markers was significantly higher in silk scaffold group. Baert et al [ 177 ] Mouse testicular cells Alginat 3D bioprinted scaffold 40 days The elongated spermatids were detected in 66% of TC/CFS, round and elongated spermatids were found in all and 33% of CD49f + /CLS constructs.…”
Section: Decellularized Extracellular Matrix Scaffoldsmentioning
confidence: 99%
“…After 1 week of culture, SSCs colonies were slowly formed. The results showed that the expression of VASA, DAZL, and Piwil2 markers was significantly higher in silk scaffold than the control group [ 153 ] (Table 1 ).…”
Section: Electrospinning Scaffoldsmentioning
confidence: 99%